Increasing "Object-Substitution" Symbolic Play in Young Children With Autism Spectrum Disorders. Issue 1 (January 2019) - Lee, Gabrielle T.; Feng, Hua; Xu, Sheng; Jin, Shao-Ju
Children with autism spectrum disorders (ASD) may not develop symbolic play skills, so such skills need to be taught specifically. We report an experiment regarding a procedure targeting "object-substitution" symbolic play skills. The "object-substitution" symbolic play behavior occurred when the child labeled a common object with the name of a substitute and used the object to perform a play action (e.g., As she put a bowl on her head, she called it a hat). A multiple probe across behaviors design was employed with five children (four boys and one girl, aged 3 to 6 years) with ASD. All children had verbal communication and demonstrated functional play and generalized imitation, but no symbolic play skills prior to the study. The instruction consisted of intraverbal training, picture prompts, and modeling of play actions. All children demonstrated object-substitution symbolic play skills after the instruction. The occurrences of response generalization were also discussed.